(untitled) (Journal of Fatima Jinnah Medical University, 2018)
A severe burn injury has strong correlation with mortality and morbidity affecting mankind all over the world since antiquity to the present era of modern science. OBJECTIVE: This study was done to find out the etiology and extent of burn injuries and its mortality in different age and gender groups, manner of death in Lahore and to compare it with other national as well as international studies. MATERIALS AND METHODS: 65 cases of death due to burn injurers were selected from all medicolegal autopsies conducted in the department of Forensic Medicine KEMU Lahore during Jan2006 to Dec 2008.Findings were tabulated from police papers, hospital records and autopsy reports. OBSERVATIONS: 65 cases of death due to burn injuries constituted 2.18 % of total autopsies conducted during the study period of 3 years at the department of Forensic Medicine KEMU Lahore. Highest incidence 44.61% was seen in 3rd decade. Females showed higher incidence 53.12% in 3rd decade. Overall males showed higher preponderance50.76% than females 49.23%.Dry flame burns gave higher incidence 69.23% followed by electric burns 23.07% then scalds 4.61% and chemical burns 3.07%.No mortality was seen under 20% total burn surface area. Majority of cases were in the range of 31% to80% TBSA. Suicidal incidence was7.69%. Homicidal incidence 38.46% was superseded by accidental incidence 53.84%.Chest and abdomen involvement was seen in 73.84% and66.15% cases respectively followed by upper limb, neck, head and face showing 55.38%,53.84%,and 46.15% cases respectively. Maximum cases 67.69 % were seen in winter season RECOMENDATIONS: The mortality and morbidity can be reduced through efforts of the Governonment and NGO’s creating awareness and education of the public. The role of media cannot be ignored in this scenario.